Impacts of photovoltaic distributed generation location and size on distribution power system network - N., Md. Saad; Muhamad Zahim, Sujod; Hui Ming, Lee; M. F., Abas; M. S., Jadin; M. R., Ishak; Nor Rul Hasma, Abdullah (Institute of Advanced Engineering and Science (IAES), 2018)
As the rapid development of photovoltaic (PV) technology in recent years with the growth of electricity demand, integration of photovoltaic distributed generation (PVDG) to the distribution system is emerging to fulfil the demand. There are benefits and drawbacks to the distribution system due to the penetration of PVDG. This paper discussed and investigated the impacts of PVDG location and size on distribution power systems. The medium voltage distribution network is connected to the grid with the load being supplied by PVDG. Load flow and short circuit calculation are analyzed by using DigSILENT Power Factory Software. Comparisons have been made between the typical distribution system and the distribution system with the penetration of PVDG. Impacts in which PVDG location and size integrates with distribution system are investigated with the results given from the load flow and short circuit analysis. The results indicate positive impacts on the system interconnected with PVDG such as improving voltage profile, reducing power losses, releasing transmission and distribution grid capacity. It also shows that optimal locations and sizes of DGs are needed to minimize the system’s power losses. On the other hand, it shows that PVDG interconnection to the system can cause reverse power flow at improper DG size and location and increases short circuit level.